2014
DOI: 10.1155/2014/419410
|View full text |Cite
|
Sign up to set email alerts
|

Sex Ratio Estimations of Loggerhead Sea Turtle Hatchlings at Kuriat Islands, Tunisia: Can Minor Nesting Sites Contribute to Compensate Globally Female-Biased Sex Ratio?

Abstract: Hatchling sex ratios in the loggerhead turtle Caretta caretta were estimated by placing electronic temperature recorders in seven nests at Kuriat islands (Tunisia) during the 2013 nesting season. Based on the mean temperatures during the middle third of the incubation period, and on incubation duration, the sex ratio of hatchlings at Kuriat islands was highly male-biased. Presently, the majority of hatchling sex ratio studies are focused on major nesting areas, whereby the sex ratios are universally believed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…Variation in the measured amount of metabolic heat is marked, but clear patterns emerged; metabolic heat warms nests above the temperature of the surrounding sand, increases throughout incubation, and peaks (averaging around 2.5 • C) 0-9 days before hatchlings emerge from the nest. Metabolic heat also varies within and between species with metabolic heat in the final semester ranging from 1.2 • C in loggerhead nests (Jribi and Bradai, 2014) to 4-8 • C in leatherback nests (Binckley et al, 1998). While most studies measured metabolic heat as the difference in temperature between the clutch and the adjacent sand at the same depth, the placement of temperature loggers within the nest and at reference sites was inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variation in the measured amount of metabolic heat is marked, but clear patterns emerged; metabolic heat warms nests above the temperature of the surrounding sand, increases throughout incubation, and peaks (averaging around 2.5 • C) 0-9 days before hatchlings emerge from the nest. Metabolic heat also varies within and between species with metabolic heat in the final semester ranging from 1.2 • C in loggerhead nests (Jribi and Bradai, 2014) to 4-8 • C in leatherback nests (Binckley et al, 1998). While most studies measured metabolic heat as the difference in temperature between the clutch and the adjacent sand at the same depth, the placement of temperature loggers within the nest and at reference sites was inconsistent across studies.…”
Section: Discussionmentioning
confidence: 99%
“…A Kruskal-Wallis H-test showed a significant difference in mean metabolic heat between trimesters of incubation, χ 2 (2) = 28.23, p < 0.001, with mean metabolic heat of 0.5 ± 0.2 • C (standard error) in the first trimester of incubation, rising to 0.9 ± 0.1 • C in the middle trimester, and 2.6 ± 0.3 • C in the final trimester ( Figure 2). Variation in metabolic heat was greatest in the final trimester, ranging from 1.2 • C in loggerhead nests (Kuriat Island, Tunisia) (Jribi and Bradai, 2014) to 4-8 • C in leatherback nests (Playa Grande) (Binckley et al, 1998). One study estimated metabolic heat generated by olive ridley embryos from a thermal balance model based on temperatures measured at the center of a nest, and in the sand above and beside the nest (Sandoval et al, 2011).…”
Section: Metabolic Heat Measured In Natural Nestsmentioning
confidence: 99%
“…Interestingly, gonadal histology as a direct sexing method, although possibly biased by the field sampling protocols and applied only in a limited number of cases, showed less skewed loggerhead hatchling sex ratios (55.6 to 79% females; see Table S18). Male-biased hatchling production oc curs at least in some sites, such as Marathonissi beach in Zakynthos, Greece (Margaritoulis 2005, Zbinden et al 2007a, Margaritoulis et al 2011a and Kuriat Island in Tunisia (Jribi & Bradai 2014), and may be possible at other sites in some years (e.g. Lakonikos Bay in Greece; Dalyan, Kizilot and Patara in Turkey) (Godley et al 2001b).…”
Section: Sex Ratiomentioning
confidence: 99%
“…Loggerhead (Zbinden et al, 2007) Zakynthos 29.3 T Piv previously calculated for same population (Mrosovsky et al, 2002) Loggerhead (Öz et al, 2004) Turkey 29 T piv previously calculated for same population (Kaska et al, 1998) Loggerhead (Hanson et al, 1998) Florida 29 T piv previously calculated for same population (Mrosovsky, 1988) Loggerhead (Tanner et al, 2019) Cabo Verde 29.25 T piv previously calculated for different population (Marcovaldi et al, 1997) Loggerhead (Jribi & Bradai, 2014) Tunisia 29.7 T piv previously calculated for different population (Mrosovsky et al, 2002) shown to evolve from the philopatric nature of sea turtles, as previously demonstrated for immune genes (Stiebens et al, 2013) and even feeding strategies (Cameron et al, 2019). For instance, green sea turtle hatchlings from dark sand (high temperature) beaches on Ascension Island grow faster and have higher levels of hatching success than those from nearby white sand (cool) beaches when exposed to hot artificial incubation environments (Weber et al, 2012).…”
Section: Ts D In S E a Turtle S: Adap Tive P Otentialmentioning
confidence: 99%